1998
DOI: 10.1002/j.1556-6676.1998.tb02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Work Transition Outcomes for Students With Disabilities: Implications for Counselors

Abstract: This study examined predictors of postsecondary school success by analyzing a 5‐year database of 2,258 students with disabilities participating in the Marriott Foundation's “Bridges…from school to work” internship programs at 6 national sites. Discriminant analysis revealed that acceptance of a job offer was predicted by internship completion, numbers of hours worked, and days absent during the internship. Internship completion and acceptance of a job offer were predictive of follow‐up employment status. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 19 publications
(19 reference statements)
0
43
0
Order By: Relevance
“…Research has shown that a previous paid or unpaid work experience is a significant predictor of job retention (Colley & Jamison, 1998;Fabian, et al, 1998;Karpur, et al, 2005). Level of education, income, health, and perceptions of disability also had a significant impact on job retention in several studies (Colley & Jamison, 1998;Fabian, et al, 1998;Hasnain & Balcazar, 2009). …”
Section: Among Many Others)mentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that a previous paid or unpaid work experience is a significant predictor of job retention (Colley & Jamison, 1998;Fabian, et al, 1998;Karpur, et al, 2005). Level of education, income, health, and perceptions of disability also had a significant impact on job retention in several studies (Colley & Jamison, 1998;Fabian, et al, 1998;Hasnain & Balcazar, 2009). …”
Section: Among Many Others)mentioning
confidence: 99%
“…Other significant factors include having prior work experience (Colley & Jamison, 1998;Fabian, 2007;Wagner, et al, 2005), having participated in vocational education (Karpur, Clark, Caproni, & Sterner, 2005), and having a career goal (Benz, Lindstrom, & Yovanoff, 2000). In addition, age, sex, stability of home environment, receiving Supplemental Security Income (SSI), staying in high school, and having an employed sibling also affect whether or not youths with disabilities secure a job during their transition from high school (Fabian, 2007;Fabian, Lent, & Willis, 1998;Gardecki, 2001;Wagner, et al, 2005).…”
Section: Among Many Others)mentioning
confidence: 99%
See 3 more Smart Citations